STRATEGIES FOR MANAGING CONFLICT IN AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This present paper proffers some suggestions on how organisations can manage conflict so that it does not disrupt their operations. Conflict, if not dealt with properly, can cause serious damage to an organisation. A huge amount of energy can go into internal conflicts, petty disputes and personal battles. Good managers spot conflicts as or even before they arise and deal with them as effectively and efficiently as if they were dealing with fires in the building. Organisations are living systems consisting of interacting units performing a task in a mutually dependant manner within a structure of scarce resources. It seems common place to suggest that conflicts would be present in such a setting. The parties in an organisation may have a conflict about the distribution of resources, or they may have a more fundamental conflict about the very structure of their organisation and the basic nature of their interaction. Once the parties are in a situation of goal incompatibility, their conflict develops in a dynamic fashion, initiating valuable and much-needed constructive changes or leading to escalating strategies and destructive consequences. Managers must accept the need to influence the developmental dynamics of a conflict so that the parties’ attitudes and actions will lead to better coordination and a more appropriate interdependence. They must not seek to stifle or eliminate organisational conflict; for that is hardly a realistic goal. The challenge managers face is to utilise such conflict management techniques that would ensure that as a conflict passes from a latent to a manifest phase, it proceeds towards its potential and realizes its constructive values.